MATERNAL CHARACTERISTICS AND COMPLEMENTARY FEEDING FOR CHILDREN UNDER 2 YEARS OLD: A CORRELATION STUDY IN TLATAH VILLAGE, PURWOSARI, BOJONEGORO - Resawati Intan Savitri; Dani Nasirul Haqi (Sekolah Ilmu Kesehatan Dan Ilmu Alam (SIKIA), Universitas Airlangga, 2021)
Background: Complementary feeding (MPASI) is substitute meals for 6 months old child to meet nutritional needs that are no longer sufficient by exclusive breastfeeding. There are several factors that can affect the delivery of MPASI by maternal namely, maternal age, level of education dan maternal occupation. Purpose: The purpose of this study is to find out the relationship between maternal age, education and occupation towards the provision of MPASI in children aged 0-2 years. Method: This research is a quantitative research with d analytics using cross sectional design. Variable characteristics of the maternal include; age, level of education and occupation. The population are all maternal who has children aged 0-2 years in Tlatah Village, Purwosari, Bojonegoro as many as 42 people and samples from simple random sampling techniques into 38 people. This research has passed the ethics review from Faculty of nursing Universitas Airlangga Number : 1769-KEPK. Result: based on statistical review using chi square test with α = 0,05, there is a relationship (p value = 0,000) between level of education to provision of MPASI and there are no relationship between maternal age (p value = 0,560) and maternal occupation (p value = 0,527) to MPASI. Conclusion: There is a relationship between level of education to the provision of MPASI and There is no relationship between maternal age and maternal occupation to the provision of MPASI.